Analisis Pengaruh Kepemilikan Institusional, Koneksi Politik, Ukuran Perusahaan, ROE, dan Leverage terhadap Sinkronisitas Harga Saham - Mardianto Mardianto; Juniyanti Juniyanti (Faculty of Economics, Universitas Internasional Batam, 2020)
This scientific work is written to examine the effect of the independent variable towards the synchronicity of stock prices variable. The independent variables referred to in the scientific work are political connections, institutional ownership, ROE, company size, leverage, skewness and kurtosis. Author will elaborate the results of the variables in this research. The LQ45 company which is well known for its financial condition, growth prospects, and high transaction value has been chosen as sample used for this study. The sampling period ranged from 2014 to 2018, which is 5 (five) years. The financial statements and annual reports of the LQ45 company are downloaded through the site https://www.idx.co.id/. Whereas the company's information regarding weekly return needed for data processing of share price synchronicity is obtained through the website https://finance.yahoo.com/. The research data obtained are then processed using Eviews application version 10 and SPSS version 22. Results indicate that the institutional ownership variable has significant negative effect on the synchronicity of stock price. While compant size and kurtosis variables has significant positive effect on the synchronicity of stock prices. Other variables, namely political connections, Return On Equity (ROE), leverage and skewness do not have a significant relationship to the variable synchrony of stock prices.